Pembiasaan Reading Log sebagai Pendukung Gerakan Literasi Nasional (GLN) di Kecamatan Ngaliyan - Nugraheti Sismulyasih Sb; Eko Purwanti Hartati; Harmanto (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
he purpose of this service is to familiarize yourself with Reading Log (Reading Journal) as a supporter of the National Literacy Movement (GLN). The method used in this service is starting with preparing books that children will read. The books provided are tiered books so that children can choose books according to their wants and needs and prepare reading corners by preparing as many reading books as many (100 reading books) of various types reading books and tiered reading. According to the target, this service is 88% of children can get used to using the reading log. This can be seen from the 25 students who filled out the reading log in full, as many as 22 children. This proves that reading logs' habit is one of the habits to support the community literacy movement.